For what it's worth: the political construction of quality in French and Italian wine markets. (28th December 2017) - Carter, Elizabeth
Abstract: At the heart of political organization, we find weak and atomized individuals who aggregate their power to challenge concentrated power. Wine politics show us that within market economies we find the same political movements. Markets, like politics, consist of institutions that differentially embed, codify and distribute power. In the case of France, small, individually weak wine producers became powerful in the aggregate; unified French grape growers came together to force a deal with the economically dominant wine merchants. Their joint political power was institutionalized in power-sharing, state-backed corporatist producer organizations. In contrast, small Italian producers failed to cooperate systematically and aggregate their power. Stronger organization enabled the construction of an institutional comparative advantage and higher prices for regulated French terroir wines. Economic sociologists claim markets are 'socially embedded'. This article demonstrates markets are 'politically embedded': French market dominance results from effective power sharing mechanisms across the supply chain.